Total long-chain polyunsaturated n-3 fatty acids level is an independent predictive factor of breast cancer multifocality in women with positive hormone-receptors tumors. (September 2021) - Ouldamer, Lobna; Goupille, Caroline; Vildé, Anne; Arbion, Flavie; Guimaraes, Cyrille; Jourdan, Marie-lise; Bougnoux, Philippe; Body, Gilles; Chevalier, Stephan
Abstract: In a previous pilot study, we showed that polyunsaturated n-3 fatty acids of breast adipose tissues were associated with breast cancer multifocality. In the present study, we investigated biochemical, clinical and histological factors associated with breast cancer focality in a large cohort of women with positive hormone-receptors tumors. One hundred sixty-one consecutive women presenting with positive hormone-receptors breast cancer underwent breast-imaging procedures including a Magnetic Resonance Imaging prior to treatment. Breast adipose tissue specimens were collected during surgery of tumors. A biochemical profile of breast adipose tissue fatty acids was established by gas chromatography. Clinicopathologic characteristics were correlated with multifocality. We assessed whether these factors were predictive of breast cancer focality. We found that tumor size (OR = 1.06 95%CI [1.02–1.09], p < 0.001) and decreased levels in breast adipose tissue of long-chain polyunsaturated n-3 fatty acids (OR = 0.11 95%CI [0.01–0.98], p = 0.03), were independent predictive factors of multifocality. Low levels of long chain polyunsaturated n-3 fatty acids in breast adipose tissue appear to contribute to breast cancer multifocality. The present results reinforce the link between dietary habits and breast cancer clinical presentation. Highlights: We investigatedfactors associated with breast cancer focality in women with positive hormone-receptors tumors. Tumor size (OR =1.06; 95%CI[1.02–1.09], p < 0.001) is an independent predictive factor of multifocality. Decreased levels in breast adipose tissue of long-chain PUFAn-3 fatty acids is an independent predictive factor of multifocality. Low levels of long chain PUFAn-3 fatty acids appear to contribute to breast cancer multifocality. The present results reinforce the link between dietary habits and breast cancer clinical presentation.